The Role of Pancasila in Facilitating Religious Moderation in Indonesia - Saputra, Edy; Hidayat, Rahmat; Harahap, Sumper Mulia (LPPAIK Universitas Muhammadiyah Bandung, 2024)
This study explores the relationship between Pancasila values and religious moderation in Indonesia, and how these values can promote a moderate, harmonious, and tolerant religious life. As the country with the largest Muslim population, Indonesia faces challenges in maintaining religious harmony amidst diversity. Analyzing the five principles of Pancasila, the study finds that the first principle (belief in One God) and the second (just and civilized humanity) lay a strong foundation for religious moderation. The third principle (Unity of Indonesia) stresses the importance of unity despite religious differences, while the fourth (Democracy guided by wisdom) encourages interfaith dialogue to resolve conflicts. The fifth principle (Social Justice) advocates for equitable welfare without discrimination, including in religious matters. The findings suggest that Pancasila can serve as a philosophical basis for religious moderation, promoting tolerance, dialogue, and respect for religious pluralism. The study also recommends expanding Pancasila values through education, government policies, and community empowerment to enhance religious moderation understanding. However, limitations in geographic scope and sample size suggest further research is needed for a more comprehensive perspective.